World Food Prize for Swaminathan - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1987)
The first World Food Prize has been awarded by General Foods Ltd. to Dr. M.S. Swaminathan, Director of the International Rice Research Institute (IRRI). This prize is designed to recognize the personal contributions of people involved in the fight...